Universal thermodynamic relations with constant corrections for rotating AdS black holes - Shao-Wen Wei; Ke Yang; Yu-Xiao Liu (Nuclear Physics B, 2021)
In Goon and Penco (2020) [17], a universal relation between corrections to entropy and extremality was proposed. The relation was also found to exactly hold for the four-dimensional charged AdS black hole. In this paper, we extend the study to the rotating BTZ and Kerr-AdS black holes when a constant correction to General Relativity is considered for the first time. The entropy and extremality bound are calculated, and they have a closely dependent behavior with the coupling parameter of the constant correction. We confirm the universal relation for the rotating AdS black holes. Furthermore, taking into consideration of the shift of the angular momentum, we confirm one more new universal relation for the rotating cases. In particular, as a more general argument, we propose a novel universal extremal relation, which gives a universal conjecture relation between the shifted thermodynamic quantities for arbitrary black hole backgrounds. We believe that these universal relations will shed new light on the region of the quantum gravity.